The effect of coordinated jump training on the development of electrical activity in the quadriceps muscle and some biomechanical variables and accuracy of the spike in volleyball (Damu Journal of Sport Sciences, 2025)
The skill of spike hitting is considered one of the most important offensive skills in volleyball, as players rely on it primarily to score points and effectively finish attacks. Spike hitting is an offensive movement in which the player jumps and strikes the ball with power and precision towards the opponent's ground, aiming to surpass the defensive block and achieve maximum offensive effectiveness. The study aimed to prepare coordinated jumping exercises and identify their impact on the electrical activity of the quadriceps muscle and some biomechanical variables for volleyball players. To achieve this goal, the researcher used an experimental design with a single group and pre-test and post-test measurements. The research sample consisted of (8) players from the Diwaniya University team. After conducting the experiment, there were positive results that will be presented in detail in the body of the research.